Adenosine Triphosphate - Binding Cassette Transporter A1 gene polymorphism (rs1800977 and rs2230806) analysis in Oral Premalignant Disorder of South Indian Cohort - Subbiah, Usha; Sivakumar, Kaniha (Asian Pacific journal of cancer prevention : APJCP, 2025)
To evaluate the association between the ABCA1 upstream variant rs1800977 (G/A) and the missense variant rs2230806 (C/T) with oral premalignancies such as oral submucous fibrosis and leucoplakia. The rs1800977 and rs2230806 of ABCA1 were analysed using PCR-RFLP in 350 subjects including OSMF, leukoplakia and healthy controls matched with age, sex, and chewing or smoking habitual factors. The allele frequency distribution and genotypic association for homozygous wild, heterozygous and variant for the diseased groups and healthy control were examined. The influence of rs1800977 and rs2230806 on mRNA secondary structure, gene-gene and protein-protein interactions was examined. The prevalence of chewers and smokers was 67% and 58% in OSMF and leukoplakia respectively, compared to 48% among chewers in the control group. The rs1800977 variant AA had a genotype distribution of 20% for OSMF and 18% for leukoplakia, while the TT genotype of rs2230806 was 10% for OSMF and 17% for leukoplakia. The allele frequencies for both diseases were 0.35 and 0.36. The odds ratios (OR) for the heterozygous CT genotype were 2.45 (CI: 1.37-4.37, P=0.00) and 1.81 (CI:1.05-3.11, P=0.04), indicating significant associations. In silico tools indicated the variants of rs2230806 and rs2230806 had lower free energy compared to the wild type suggesting variants were more stable than the wild type on mRNA. The CT genotype of the missense SNP rs2230806 was associated with an increased risk for the disease and could serve as a valuable marker for assessing the prognosis of oral premalignancies.